Effect of first trimester maternal serum pregnancy associated plasma protein: a level on fetomaternal outcome - Singh, Shilpi; Singh, Pushpa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Serum pregnancy-associated plasma protein-A (PAPP-A) levels fluctuate in continuation with the pregnancy and thus become an important standalone marker in monitoring the adverse outcomes that may occur in pregnancy. Methods: A prospective observational study was conducted in the department of obstetrics and gynaecology. A total of 240 pregnant women in their first trimester were included in the study. Serum PAPP-A levels were measured at 11-13+6week of gestation and were evaluated with respect to the feto-maternal outcome. The data was entered in MS excel spreadsheet and analysis was done using Statistical Package for Social Sciences (SPSS) version 21.0. Results: The mean age of the study population was 27 years. Among the maternal pregnancy parameters, PIH, pre-term labor and Emergency LSCS were significantly associated with low (<0.5 MoM) Serum PAPP-A levels, P<0.05. All the fetal outcome measures: IUGR, IUD, low birth weight, SGA babies, prematurity and NICU admissions, were significantly associated with low (<0.5 MoM) Serum PAPP-A levels, p <0.05. Conclusions: Serum PAPP-A in the early pregnancy showed significant correlation with feto-maternal outcome. Thus, it has the potential to be used as a prognostic factor and in the management of adverse outcomes by increasing surveillance for pregnant women with high-risk factors.